Solid State Fermentation Parameters Effect on Cellulase Production from Empty Fruit Bunch - Vita Wonoputri; Subiantoro Subiantoro; Made Tri Ari Penia Kresnowati; Ronny Purwadi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
In this study, agriculture waste palm empty fruit bunch (EFB) was used as carbon/cellulose source in solid state fermentation for cheaper cellulase production. Fermentation operation parameters, such as: solid to liquid ratio, temperature, and pH, were varied to study the effect of those parameters towards crude cellulase activity. Two different fungi organisms, Trichoderma viride and Trichoderma reesei were used as the producers. Extracellular cellulase enzyme was extracted using simple contact method using citrate buffer. Assessment of the extracted cellulase activity by filter paper assay showed that Trichoderma viride is the superior organism capable of producing higher cellulase amount compared to Trichoderma reesei at the same fermentation condition. The optimum cellulase activity of 0.79 FPU/g dry substrate was obtained when solid to liquid ratio used for the fermentation was 1:1, while the optimum fermentation temperature and pH were found to be 30 °C and 5.5, respectively. The result obtained in this research showed the potential of EFB utilization for enzyme production.